Consolidation and characterization of Cu, Mg substituted hydroxyapatite by cold sintering - Hmood Firas J.; Sabri Israa K.; Najim Allaa S. (Science of Sintering)
Cold sintering method is an effective route to consolidate powders at temperatures below 300°C. In this study, pure and (Cu, Mg) substituted hydroxyapatite were sintered at 250°C. Ultrapure and substituted hydroxyapatite powders were synthesized by wet precipitation method. Sintering pressure of 250 MPa was used to compact the powders while they were heated simultaneously. 10% (H3PO4) solution was used as a transsolvent for the ionic-substituted hydroxyapatite while distillated water was supplied to the pure one. The yield geometries were characterized for density, thermal stability, microstructure, and the biodegradation in Tris-HCl buffer. The findings indicate that the pure hydroxyapatite compacts has a density of 2.876 g/cm3 (86% TD). Owing to the low sintering temperature the resulting hydroxyapatites have not experienced thermal decomposition, besides no additional phases have appeared. Biologically, the sintered sample (Cu0.25Mg0.75Ca9(PO4)6(OH)2) showed larger degradability (0.0001 g/mm2) than to others after one day of immersion.